2016
DOI: 10.1177/0269215515603218
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Kinesio taping application for acute non-specific low back pain: a randomized controlled clinical trial

Abstract: Kinesio taping provided significant improvements in pain and disability; thus, it can be used as a complementary method in acute non-specific low back pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
35
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 19 publications
0
35
0
Order By: Relevance
“…The findings of the current study indicate that KT is superior to other methods, including no taping, acupuncture and other general physical therapy methods, for CNSLBP patient treatment, with reduced VAS and ODI. Similarly, Kelle et al demonstrated a significant improvement in pain control in a KT group compared with a control group for patients with acute non-specific low back pain (29). A RCT study conducted by Forozeshfard et al demonstrated that KT significantly reduces pain and functional disability in young females with menstrual low back pain (30).…”
Section: Discussionmentioning
confidence: 99%
“…The findings of the current study indicate that KT is superior to other methods, including no taping, acupuncture and other general physical therapy methods, for CNSLBP patient treatment, with reduced VAS and ODI. Similarly, Kelle et al demonstrated a significant improvement in pain control in a KT group compared with a control group for patients with acute non-specific low back pain (29). A RCT study conducted by Forozeshfard et al demonstrated that KT significantly reduces pain and functional disability in young females with menstrual low back pain (30).…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, there are also studies which investigated the effect of KT application for acute back pain. [30] In a study by Kelle et al, [30] 109 patients with acute non-specific low back pain were included and randomized into either KT or placebo groups; both groups received merely information and reassurance. KT was applied for 12 days.…”
Section: Discussionmentioning
confidence: 99%
“…The use of Kinesio Taping (KT) has steadily increased in clinical practice among physical therapists, and its effectiveness has recently been assessed in acute and/ or chronic nonspecific LBP [9][10][11]. KT is an inexpensive, and easy-to-use treatment method because of its ease and speed of application [11].…”
Section: Introductionmentioning
confidence: 99%